Analisis Kapasitas Saluran Drainase terhadap Debit Rencana di Kelurahan Bidara Cina, Kecamatan Jatinegara, Jakarta Timur - Anastasia Septya Wardaningrum; Jalaludin Jalaludin; Stevi Cahyani (Yayasan Literasi Sains Indonesia, 2026)
Bidara Cina is a flood-prone area in East Jakarta due to high rainfall, limited channel capacity, and low elevation along the Ciliwung River. This study analyzes the existing drainage channels' capacity to accommodate design runoff discharge based on BMKG rainfall data and hydrological parameters. Methods include calculating design rainfall intensity (Gumbel/Mononobe method), design discharge (Rational Method), and existing capacity (Manning’s formula) using secondary data from BMKG, BIG, BPS, and East Jakarta Water Resources Sub-department. Main channel segments were selected as representative samples. Based on frequency analysis of 20-year extreme data (2006–2025) from Halim Perdanakusuma Station, the design rainfall intensity is 78.71 mm/hour for a 5-year return period and 96.60 mm/hour for a 10-year return period. Evaluation of 15 channel segments shows that macro channels (Ciliwung River and Ciliwung Waterway) and the main connecting channel (West Otista Raya Street) meet the required capacity. However, 7 secondary channel segments in densely populated areas (RW 06, RW 07, and RW 11) fail to meet capacity or overflow due to narrow dimensions and the lack of local retention polders.